Adopting price-level targeting under imperfect credibility: An update - Oleksiy Kryvtsov; Malik Shukayev; Alexander Ueberfeldt (Bank of Canada, 2008)
This paper measures the welfare gains of switching from inflation-targeting to price-level targeting under imperfect credibility. Vestin (2006) shows that when the monetary authority cannot commit to future policy, price-level targeting yields higher welfare than inflation targeting. We revisit this issue by introducing imperfect credibility, which is modeled as gradual adjustment of the private sector's beliefs about the policy change. We find that gains from switching to pricelevel targeting are small. A welfare loss occurs, if imperfect credibility is highly persistent.
Keywords: E31; E52; 330; Credibility; Monetary policy framework; Geldpolitisches Ziel; Zentralbank; Inflation Targeting; Preisniveau; Glaubwürdigkeit; Wohlfahrtseffekt; Theorie